Sedimentology and Petrography of the Mamuniyat Formation, Elephant Oil Field Concession NC174, NW Murzuq Basin, SW Libya - A. A. Kushlaf; A. Shiwa; Yahia A. Salem (Surman Journal of Science and Technology, 2024)
This research aims to study the sedimentary and petrography interpretation of the Mamouniyat Formation in the El Feel oil field, concession NC174 in the Murzuq Basin through investigation and analysis of core samples, wireline log data and conventional core analysis for the key well (F2-NC174) located on the western part of E.O Field. The Mamouniyat Formation has been Lithostratigraphically divided into three members based on grain size and wireline log response. Five facies have been known in the Mamouniyat Formation, according to specific associations with rock types and their lithological and sedimentological characteristics. All these facies were collected into three different facies associations. The sandstone is internally structured by symmetrical to asymmetrical wave ripples and parallel lamination. The Petrographic study indicate that the Mamuniyat Formation consists primarily of sublitharenite rocks with the presence of some litharenites and quartiz arenites. The studies also made it clear that the average Mamuniyat porosity is approximately ranging from medium to good porosity.